2009
DOI: 10.1007/s11104-008-9866-z
|View full text |Cite
|
Sign up to set email alerts
|

Do tree species characteristics influence soil respiration in tropical forests? A test based on 16 tree species planted in monospecific plots

Abstract: The high spatial variability of soil respiration in tropical rainforests is well evaluated, but influences of biotic factors are not clearly understood. This study underlines the influence of tree species characteristics on soil respiration across a 16-monospecific plot design in a tropical plantation of French Guiana. A large variability of soil CO2 fluxes was observed among plots (i.e. 2.8 to 6.8 μmol m−2 s −1 ) with the ranking being constant across seasons. There were no significant relationships between s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 57 publications
2
55
1
2
Order By: Relevance
“…According to the patch-scale process of litter decomposition, individual microcosms were considered as independent replicates just as in most litterbag studies. Moreover, previous studies in the plantation (Bréchet et al 2009) and in the nearby natural forest (Hättenschwiler and Bracht Jørgensen 2010;Fanin et al 2011) showed substantial variation in soil processes and decomposition at very small spatial scales that was as large or larger within blocks at the Oecologia (2011) 167:241-252 243 meter scale than among blocks of hundreds of meters distance (Fanin et al 2011).…”
Section: Plant Materials and Experimental Designmentioning
confidence: 92%
See 1 more Smart Citation
“…According to the patch-scale process of litter decomposition, individual microcosms were considered as independent replicates just as in most litterbag studies. Moreover, previous studies in the plantation (Bréchet et al 2009) and in the nearby natural forest (Hättenschwiler and Bracht Jørgensen 2010;Fanin et al 2011) showed substantial variation in soil processes and decomposition at very small spatial scales that was as large or larger within blocks at the Oecologia (2011) 167:241-252 243 meter scale than among blocks of hundreds of meters distance (Fanin et al 2011).…”
Section: Plant Materials and Experimental Designmentioning
confidence: 92%
“…Soils are nutrient-poor acrisol developed on a Precambrian metamorphic formation called the Bonidoro series. Soil characteristics are broadly the same in the plantation (Roy et al 2005;Bréchet et al 2009) and the natural forest (Hättenschwiler and Bracht Jørgensen 2010) with a similar texture, and similar concentrations of carbon (16.2 and 18.7 g C/kg in the plantation and the natural forest, respectively), nitrogen (1 and 1.2 g N/kg), and phosphorus (0.006 and 0.0055 g ''Olson P''/kg). The tree canopy in the plantation is somewhat more open (mean leaf area index of about 4; Roy et al 2005) than in the natural forest (leaf area index of about 6; Handa et al, unpublished data).…”
Section: Study Sitementioning
confidence: 92%
“…Each week, four out of sixteen chambers were programmed to stay closed for a longer measurement period to ensure a reliable estimation of low fluxes while the other twelve chambers were 20 programmed to stay closed for a shorter period to capture diel variation and detect high fluxes. For the short closure time (SHORT hereafter), we used a 2 minute measurement period because (1) this is a standard closure time for soil CO2 flux calculations (Janssens et al, 2000), even in tropical forests (Epron et al, 2006;Sayer et al, 2007) of this region where MDF for CO2 flux is typically low (Bonal et al, 2008;Bréchet et al, 2009;Courtois et al, 2018), (2) ) are compatible with the detection of emission or consumption peaks of these 25 two gases in this region (Courtois et al, 2018;Petitjean et al, 2015). For the long closure time (LONG hereafter), we decided to use a 25 minute measurement period in order to optimize the trade-off between a reliable estimation of low N2O fluxes (Table 1) and a program length that allows for a sufficient number of flux measurements per chamber and per day.…”
Section: Closure Timementioning
confidence: 99%
“…Wang et al, 2013), and tropical rainforests (Bréchet et al, 2009). In our study, despite similar T s and SWC, R s of the native MP was 24% higher than the exotic SP.…”
Section: Soil Co 2 Efflux and Components Of Native And Exotic Tree Spmentioning
confidence: 99%